Triterpenoid saponins from the herb Hylomecon japonica. (January 2021) - Li, Fei; Wu, Si-Tong; Qu, Ming-Hui; Wang, Yi-Xiao; Ma, Chun-Liu; Yu, Bai-Hong; Wang, Guang-Shu
Abstract: Six undescribed triterpenoid saponins, named as hylomeconoside C–H, were isolated from the EtOH extract of Hylomecon japonica . On the basis of spectroscopic and chemical evidence, their structures were identified as 3- O -β-D-galactopyranosyl-(1 → 2)-β-D-glucuronopyranosyl gypsogenin 28- O -α-L-rhamnopyranosyl-(1 → 2)-β-L-arabinopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-L-arabinopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-[α-L-arabinopyranosyl-(1 → 3)]-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-glucopyranosyl-(1 → 3)-[β-D-xylopyranosyl-(1 → 4)]-α-L-rhamnopyranosyl-(1 → 2)-β-L-arabinopyranoside; 3- O -β-D-galactopyranosyl-(1 → 2)-β-D-glucuronopyranosyl gypsogenin 28- O -β-D-galactopyranosyl-(1 → 3)-[β-D-xylopyranosyl-(1 → 4)]-α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside; 3- O -α-L-rhamnopyranosyl-(1 → 3)-[β-D-galactopyranosyl-(1 → 4)]-β-D-glucuronopyranosyl quillaic acid 28- O -β-D-galactopyranosyl-(1 → 3)-[β-D-xylopyranosyl-(1 → 4)]-α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranoside; 3- O -α-L-rhamnopyranosyl-(1 → 3)-[β-D-galactopyranosyl-(1 → 4)]-β-D-glucuronopyranosyl quillaic acid 28- O -β-D-xylopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-quinovopyranoside. The 50% EtOH extract showed moderate inhibitory activity on the human cancer cell line HeLa, HepG-2, MCF-7, A549, K562 and TE-1. And these six compounds were tested for cytotoxicity against K562. Among them, hylomeconoside H was found to be the most active on the K562 cell lines (IC50 6.60 μM). Graphical abstract: Hylomeconoside C–H (1–6) isolated from Hylomecon japonica (Thunb.) Prantl & Kündig, The picture come from the academic dissertation by Wang J, studies of saponins from Hylomecon japonica (Thunb.) Prantl et Kündig (Ⅰ). Image 1 Highlights: Six undescribed oleanane-type triterpenoid saponins, were isolated from Hylomecon japonica. Their structures were elucidated by 1D, 2D-NMR and HRESIMS analyses. The triterpene saponins showed selective and moderate cytotoxicities against human leukemic cancer cell line K562.